2016
DOI: 10.1111/jnc.13571
|View full text |Cite
|
Sign up to set email alerts
|

Multisite tyrosine phosphorylation of the N‐terminus of Mint1/X11α by Src kinase regulates the trafficking of amyloid precursor protein

Abstract: Mint/X11 is one of the four neuronal trafficking adaptors that interact with amyloid precursor protein (APP) and are linked with its cleavage to generate b-amyloid peptide, a key player in the pathology of Alzheimer's disease. How APP switches between adaptors at different stages of the secretory pathway is poorly understood. Here, we show that tyrosine phosphorylation of Mint1 regulates the destination of APP. A canonical SH2-binding motif

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…Our observations are in agreement with the finding of various mass spectrometric studies, namely, that GULP1 is a phosphoprotein (26)(27)(28). It has been reported that phosphorylation of AIPs alters APP processing, including residues within their PTB domains (14,19,29,30). Five phospho-residues within the GULP1 PTB domain have been reported in several mass spectrometric studies (26)(27)(28).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are in agreement with the finding of various mass spectrometric studies, namely, that GULP1 is a phosphoprotein (26)(27)(28). It has been reported that phosphorylation of AIPs alters APP processing, including residues within their PTB domains (14,19,29,30). Five phospho-residues within the GULP1 PTB domain have been reported in several mass spectrometric studies (26)(27)(28).…”
Section: Resultssupporting
confidence: 93%
“…It has been reported that phosphorylation of AIPs alters APP processing, including residues within their PTB domains (14, 19, 29, 30). Five phospho‐residues within the GULP1 PTB domain have been reported in several mass spectrometric studies (2628).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is supported by the fact that mAtg9 can be phosphorylated by Src kinase which facilitates the interaction between Atg9 and AP1/AP2. Because it is known that multiple members of Src kinase family cycle between the plasma membrane, the Golgi complex, and the endosomes [41][42][43], and are involved in the transport of various cargoes between these membrane compartments [44,45]. When it is still unclear why abolishing the Src-dependent phosphorylation that prevents mAtg9 from interacting with AP1 and AP2, can increase mAtg9 on the plasma membrane [31], our data suggest that the phosphorylation contributes to the post-Golgi transport of cathepsin D. The phosphorylation of mAtg9 may occur either on the plasma membrane or on the TGN by activated Src from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…APP-dependent modulation of synaptic structure and function may occur through alternative splicing of APP or phosphorylation of the APP C-terminus, thereby altering interaction of APP/APLP with their binding proteins (Kyriazis et al, 2008; Tamayev et al, 2009; Dunning et al, 2016). Alternative splicing of APP and its homologs is complex, but detailed investigations in the context of the putative physiological functions of APP are lacking (Pandey et al, 2016).…”
Section: App/aplp Binding Proteins and Synaptic Functionmentioning
confidence: 99%